Differential Hydro-Mechanical Transmissions with Hydrostatic Units - Brumercik, Frantisek; Kocur, Roman; Pazican, Milan; Lukac, Michal (Communications - Scientific letters of the University of Zilina, 2005)
At present, hydromechanical transmissions are used especially in agricultural and defence vehicles. These transmissions have potential to be used also in other vehicles, for example commercial cars and buses. Differential hydromechanical transmission generation needs to achieve comparable parameters in comparison with the competition to prove maximum of drive comfort, safety, reliability and efficiency.